Problematika Teori Hukum, Konstruksi Hukum, dan Kesadaran Sosial - Ilham Yuli Isdiyanto (Jurnal Hukum Novelty, 2018)
This theoretical-normative study aims to determine the problematic use of legal theory and its impact on the construction of the law itself. This is very important because the construction of today's law has not created a social awareness of the law so that law enforcement becomes difficult. The discussion in this study raises several issues to be studied, such as; what is the dependencies pattern between law and social awareness? Then how to reconstruct them in the current of the Theory of Law? And the last is; what is the proper direction of legal creation? The results of this study conclude: First, the problem of alienation and distortion between law and society is just like an iceberg phenomenon because the main problem lies within the understanding theoritical of the law itself. Second, the relationship between law and social awareness is the dependence relationship, where the legal product must reflect social awareness so that the actualization of the law is accepted by society as its need. Third, discussing the correlation between law and society is not enough with normative thought (prescriptive), but also empirical (descriptive), so the theory of law plays a very important role to bring this multidisciplinary understanding back to normative thought that prescriptive. Fourth, the legal product which is not based on normative thought is very dangerous because it will be very liberal and far from social morality based on social values, thus there will be alienation and distortion between law and society, or in other words law does not reflect the social awareness.